Among The Wild Mulattos and Other Tales - Williams, Tom (Thomas S.) (Book collections on Project MUSE., 2015)
Set in the suburbs and cities of the Midwest, Mid-South, and Texas, these stories explore the lives of characters biracial, black, white, and all sorts of in-between. The intersections and collisions of contemporary life are in full effect here, where the distinctions between fast food and fine art, noble and naked ambitions, reality and reality shows have become impossible to distinguish. Read these stories and understand why Steve Yarbrough said Williams "writes like Paul Auster if he were funnier or like Stanley Elkin might have if he'd ever been able to stop laughing." " Tom Williams has done the near impossible in penning a book that is both undeniably entertaining and deeply thoughtful, Millhauser meets Bukowski meets Ellison." --Alan Heathcock, author of Volt "Sure, we need the nudge of category to help us all think straight, but we also need the rangy trickster, Tom Williams, to do the bang-up boundary work of imaginary anthropology in these deadpan dead-on gems. These infiltrating texts take us sideways, through and through, turn us inside-out." . --Michael Martone, author of Michael Martone and Four for a Quarter. --Provided by publisher.